LITERARY AND INTELLECTUAL LIFE IN NINETEENTH-CENTURY PENYENGAT ISLAND, RIAU:: The Works of Raja Ali Haji - Mohd Noor, Arba'iyah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
Malay society has a variety of historical heritages one of which is Malay manuscripts. They are valuable treasures containing knowledge that informs the world about the soul, spirit, thinking, and civilisation of the Malays, and that will be of interest to future generations. This article introduces the works of Raja Ali Haji of Penyengat Island (c. 1808 – c. 1873), one of the great Malay writers of the nineteenth century, and will briefly discuss the history of Bugis domination in the Johor-Riau Lingga region in the eighteenth century. The discussion will also cover the development of Malay historiography and literary activities in the early nineteenth century to which Raja Ali Haji and other scholars brought about significant changes. The findings of the study reveal that he was a prominent figure not only in the aspect of religion but also in literature, language, politics, and history. His prowess was inherited by his family and descendants who formed a movement known as the Rusydiah Club to stimulate feelings of nationalism among the community with the view of opposing the Dutch in Riau.